Nikah Sirri (Perbandingan Hukum Positif Indonesia Dan Hukum Islam) - Fajrina Dhia Salsabila; Vanda Kamila Alfi Syahri; Tutik Hamidah; Kasuwi Saiban (An-Nisa: Journal of Islamic Family Law, 2025)
The implementation of Marriage Act No. 1/1974, which was later amended by Act No. 16/2019, and its various provisions, led to the emergence of the phenomenon of nikah siri. Nikah siri is a marriage that takes place in secret and is not registered in accordance with the provisions of the current Marriage Law. This research will include an in-depth analysis of 1) An explanation of nikah siri according to Indonesian positive law and Islamic law. 2) The legal status and criminal sanctions of nikah sirri under Indonesian positive law and Islamic law. This research is normative in nature with a comparative approach to analyse the crime of nikah sirri by comparing Indonesian positive law and Islamic law. The data collected will be analysed descriptively and comparatively to identify the similarities, differences and legal implications of the crime of nikah sirri in the two perspectives. Therefore, it is hoped that this research can increase understanding of the phenomenon and make a positive contribution to our knowledge of the dynamics of human relationships in the context of hidden marriages.